True Hamsters (Cricetinae) of the Palaearctic Region - Kryštufek, Boris; Shenbrot, Georgy Isidorovich (University of Maribor Press, 2025)
True hamsters are a small subfamily (Cricetinae) containing only 19 species which are endemic to the Palaearctic region. Despite such low species richness, general public is well familiar with hamsters, primarily knowing them as pets, experimental laboratory animals and species of conservation concern. The present work is a compilation integrating achievements of the genomic era with the traditional taxonomy. The aim was to provide an authoritative and up-to-date taxonomic guide to the animal group, which is of great interest to experts engaged in medical zoology, epidemiology, biostratigraphy, zooarchaeology, evolutionary research, population ecology, animal systematics, biodiversity conservation, museum collection management and many more biological subdisciplines. The most significant original contribution is perhaps revision of the family-group taxa with naming 2 new subtribes and 2 new tribes. The text is supplemented by 120 illustrations and over 700 references. Morphological details of skull and dentition of each of the 19 species are depicted, and their distributions are mapped in detail. The book will allow the user to interpret intelligently the taxonomic system of Cricetinae and to follow taxonomic progress with a critical eye.